Succession Plans: Is there a Biblical Template?. Issue 2 (2nd July 2016) - Pugh, Ben
Abstract : Since the 1990s, the issue of succession has been a pressing one in the UK throughout what are now commonly referred to as the 'Apostolic Networks', the networks of neo-Charismatic churches that developed out of the House Church movement and which laid particular stress upon present-day apostles. Within an avidly relational and informal structure, the government of each of these networks resides to a significant extent within key apostolic leaders. Over the last twenty years, almost all of these networks arrived at a situation in which they were overseen by a still energetic yet ageing apostle and with no obvious successor to hand. The beginnings of the networks were often associated with big personalities, credited with high apostolic gifts. The Old Testament similarly abounds with anointed kings and prophets and their successors who were sometimes very unsubtle in the way they then wielded the power bequeathed to them. The New Testament centres on a founder whose act seems especially hard to follow. This study will seek to synthesize the biblical data, and what it implies about how to do it and how not to do it, into a form that can be the biblical basis for Pentecostal and charismatic leadership transition today.